Factors Influencing Behavioral Propensity To Use Mobile Shopping Apps In Generation X: The Tam Approach - Rafnelly Rafki; Nofriadi Nofriadi; Yolanda Oktarina; Nurhaida Nurhaida; Rinda Lestari; Nova Mustika (ARRUS Journal of Social Sciences and Humanities, 2023)
The purpose of this study was to study the factors that influence the intention of Generation X in using online shopping applications, with the TAM (Technology Acceptance Model) approach. This research is a survey research using questionnaires as a tool to collect data. Pre-testing is carried out at the beginning of the study, before distributing questionnaires to ensure that the instruments used are valid and understandable. The 50 respondents were Generation Xers aged 43 to 58, who used online shopping applications. The instrument is a questionnaire consisting of two parts, namely the independent variable and the dependent variable. The data were analyzed with SEM, and validity and reliability tests were conducted. What influences Generation X's intention to shop on online shopping apps is 1. perception of usefulness, 2. perception of ease of use,3. perception of value and 4. perception of security. In addition, social factors such as subjective norms and reference groups. This research can help e-commerce companies improve services to Generation X consumers, by making it easier for them to use online shopping applications.